2018
DOI: 10.1007/s10068-018-0485-z
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals concentration and human health risk assessment in seven commercial fish species from Asafo Market, Ghana

Abstract: Health risk assessment and heavy metal accumulation were evaluated in the muscles of widely consumed Trachurus trachurus, Lutjanus fulgens, Lutjanus goreensis, Acanthocybium solandri, Pagellus bellottii, Scomber colias and Dentex congoensis fish species in Asafo, Ghana. The fish samples were prepared using a wet digestion method and the heavy metals analysis was performed with the flame atomic absorption spectrophotometer (UNICAM 969). The results revealed that Mn, Cu, Zn, Cd, and Pb concentrations were below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 51 publications
(47 reference statements)
11
13
0
Order By: Relevance
“…After normalizing to a 75% moisture level, the cadmium levels in marine species ranged from approximately 0.009 mg/kg in African moonfish to 0.034 mg/kg in European anchovy. Kwaansa-Ansah, Nti [114] reported cadmium concentrations in marine fish fillets from Ghana ranging from 0.007 to 0.019 mg/kg, which are in accordance with the findings in this study, with only anchovy having higher concentrations. Kortei, Heymann [115] reported cadmium concentrations in fillet of two freshwater species from below detection limit up to 0.08 mg/kg, which is higher compared to the samples analyzed in this study.…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…After normalizing to a 75% moisture level, the cadmium levels in marine species ranged from approximately 0.009 mg/kg in African moonfish to 0.034 mg/kg in European anchovy. Kwaansa-Ansah, Nti [114] reported cadmium concentrations in marine fish fillets from Ghana ranging from 0.007 to 0.019 mg/kg, which are in accordance with the findings in this study, with only anchovy having higher concentrations. Kortei, Heymann [115] reported cadmium concentrations in fillet of two freshwater species from below detection limit up to 0.08 mg/kg, which is higher compared to the samples analyzed in this study.…”
Section: Plos Onesupporting
confidence: 91%
“…Consequently, future studies need to investigate sources of contamination including regional difference. No scientific papers analyzing the lead content of whole fish in Ghana were found for direct comparison, but studies of lead in muscle tissue of several freshwater species ranged from 0.04 to 0.42 mg/kg [ 115 ], 0.060–0.085 mg/kg in fillet of marine species [ 114 ] and levels lower than 0.2 mg/kg in fillet of catfish and bigeye grunt [ 120 ]. The lead concentration in dried fish products from our study was higher than levels reported for fresh fish, which is mainly caused by the reduced water content in the fish due to processing [ 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…The highest EDI value of Cd (0.0003 mg kg −1 day −1 ) was much lower than the PTDI, whose values is 0.001 mg kg −1 day −1 of body weight 48,49 corresponding to 0.0607 mg kg −1 for an adult weighing 60.7 kg. Daily Cd intake through consumption of the commonly consumed fish varieties was lower than or similar to the daily intake reported for adult consumers from other developing countries—Ghana: 0.000092 mg kg −1 day −1,58 Nigeria: 0.000063 mg kg −1 day −1,54 Ethiopia: 0.000029 mg kg −1 day −1,59 D. R. Congo: 0.00012 to 0.00094 mg kg −1 day −1,60 Egypt: 0.000048 to 0.00022 mg kg −1 day −1,61 Iran: 0.00012 mg kg −1 day −1,62 and Bangladesh: 0.00027 to 0.00246 mg kg −1 day −1 . 63 Daily Cd intake was higher than that reported for adults in Yaoundé, Cameroon, 0.000017 mg kg −1 day −1,64 and roughly 26 times higher than that reported for adults from Dares salaam, Tanzania.…”
Section: Resultsmentioning
confidence: 48%
“…Lower or similar Cu EDI values are reported in literature in the range of 0.00000066 to 0.00093 mg kg −1 day −1 . 54,58,[63][64][65] Higher daily intake of Cu through fish consumption is reported for consumers in Egypt, 0.0124 -0.0250 mg kg −1 day −1 , and Congo, 0.12586 -0.0211428 mg kg −1 day −1 . 60,61,63 As for Pb, the greatest daily intake (0.…”
Section: Trace Metal Concentrations In the Commonly Consumed Fish Spementioning
confidence: 99%
See 1 more Smart Citation